Optimisation of 3D intestine model & TK6 co-culture media to aid in the development of 3D micronuclei assay to assess Food nanogenotoxicity - Lim, Michelle Jing Sin (2019)
Nanoparticles are increasingly applied in the food industry without the availability of risk assessments. To reduce animal testing in risk assessments, improvements to in vitro testing have been made over the years. Here, we aim to develop a co-culture system using 3D intestinal model and TK6 cells to study food nanogenotoxicity using cytokinesis-blocked micronucleus assay. As both cultures are grown with different media, optimisation was done to cultivate both tissue and cells in the same media to minimize changes to their native characteristics. RPMI, SMI, 10:90 and 25:75 RPMI:SMI media composition were tested on 3D tissues for 4 days and TK6 for 11 days. Using real-time PCR, both cultures had slower proliferation and were less inflamed, apoptotic and necrotic when grown in media other than their base media. For TK6, a minor and insignificant increase in the population doubling time was observed in media with SMI after 4 culture days. No changes to the basal micronuclei level in binucleated cells grown in different media compositions was seen. Furthermore, cytostasis increased throughout the culture period in all the media composition, with TK6 in SMI having the highest level of inhibition. Collectively, the results point to using SMI as the co-culture media.